Potential of prospective medicinal plants of Rhizophoraceae from North Kalimantan, Indonesia (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Egra S, Kuspradini H, Kusuma IW, Batubara I, Imra, Nurjannah, Wahyuni E, Yamauchi K, Mitsunaga T. 2023. Potential of prospective medicinal plants of Rhizophoraceaefrom North Kalimantan, Indonesia. Biodiversitas 24: 1346-1355. The abundance of mangrove forests in the equatorial region necessitates proper management, including the sustainable use of plant parts for functional products such as food, medicine, etc. This study aimed to assess the medicinal potential of five mangrove plants through phytochemical analysis, antibacterial assays against Streptococcus sobrinus, DPPH free radicals, and toxicity assay using Artemia salina L., Bruguiera parviflora(Roxb.) Wight and Arn. ex Griff, Bruguiera cylindrica(L.) Blume, Ceriops tagal(Perr.). The plants used were Ceriops tagal (Perr.) C.B. Rob, Rhizophora mucronata Poir, and Rhizophora apiculata Blume. Plant samples were extracted with n-hexane, ethyl acetate, and methanol in that order, and then the obtained plant extracts were subjected to various assays. The results showed that B. cylindrica wood and C. tagal leaf extract had the highest antibacterial activity, with more than 50% relative inhibition. The C. tagal leaf methanolic extract had the highest antioxidant activity, by 91% relative inhibition. Followed by R. mucronata wood ethyl acetate extract and B. parviflora leaf methanolic extract, with 87% and 86%, respectively. The highest value in the cytotoxicity assay was discovered in the B. cylindrica in the very strong category with an LC50value of 22.9 µg/mL. The present study revealed the potential of mangrove plant extracts to have strong antibacterial, cytotoxic, and antioxidant properties.